Climate change education: exploring knowledge, attitudes, and practices of medical students in a Turkish medical school. - Koç, Demet; Yangıncı, Kemal; Yavuz, Melike (International Journal of Health Promotion & Education, 2026)
Climate change presents a significant health challenge, emphasizing the need for resilient healthcare systems. This study aimed to explore medical students' knowledge, attitudes, and practices regarding the climate-health link and their curriculum preferences. Conducted from March to June 2023 at the Medical School of Bahçeşehir University, Turkiye, the cross-sectional study utilized an online questionnaire covering demographic data and climate change-related inquiries. Participation was open to all medical students without class-based distinctions. The response rate was 53.6%, with 439 medical students included (average age: 21.8 years). The majority (74.5%) acknowledged human-induced climate change, with over 87% expressing concerns about its impact on health. Nearly 70% emphasized the importance of physicians understanding climate change's health effects, while 45.8% perceived a lack of information in their medical education. Most students (70.0%) supported integrating climate change's health effects into medical education, rating its importance at 7.1 on a scale of 0 to 10. Preferences included electives, team-based learning, case-based learning, problem-based learning, clinical practice in climate-sensitive diseases, and theoretical courses on climate change in basic medical sciences. This study underscores the growing awareness among medical students regarding climate change's health impact and the need for climate-integrated medical education, emphasizing its importance in preparing future physicians for climate-related health challenges and resilient healthcare systems.